Dynamics and Failure Analysis on Rigid–Flexible Coupling Structure to Bucket Wheel Stacker Reclaimer - Xiaozhen Wang; Yixiao Qin; Lin Chen (Machines)
The adjustment of counterweights in bucket wheel stacker reclaimers is crucial for the equipment’s load-bearing capacity, vibration, and overall stability. To enhance operational reliability and safety while reducing failure rates and maintenance costs, this study employs finite element analysis (FEA) software and multibody dynamics (MBD) software to develop a rigid–flexible coupling model of the bucket wheel stacker reclaimer. By simulating the excavation forces generated by different materials, the dynamic response of the equipment during operation was analyzed. The results indicate that during the initial startup phase, significant fluctuations in the system’s parameters occur due to vibrations, but these stabilize after 40 s of damping. Comparative analysis of four excavation forces and various counterweight values during the reclaiming process identifies the optimal counterweight as 170 t. The study further reveals that under rotary working conditions, as the excavation force increases, the failure counterweight value increases by 8.3%. This research provides a theoretical basis for optimizing the adjustment of counterweights in bucket wheel stacker reclaimers, guiding operational practices under actual working conditions, ensuring efficient operation across different scenarios, and extending the equipment’s service life.